Catch dynamics, growth, and reproduction of striped mojarra eugerres plumieri in lake Maracaibo, Venezuela - Ferrer Montaño, Orlando José (Ciencia)
<!– /* Font Definitions */ @font-face font-family:Bookman; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-alt:"Bookman Old Style"; mso-font-charset:0; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:0 0 0 0 0 0; @font-face font-family:"SymbolProp BT"; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-alt:"Times New Roman"; mso-font-charset:0; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:0 0 0 0 0 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; a:link, span.MsoHyperlink color:blue; text-decoration:underline; text-underline:single; a:visited, span.MsoHyperlinkFollowed color:purple; text-decoration:underline; text-underline:single; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –>Catch dynamics, growth and reproductive aspects of striped mojarra were examined during a 3-year study in the El Tablazo Bay, an important estuarine system within the lake basin. Sampling was conducted semimonthly from January 2000 to December 2002 using beach seines and cast nets. Fluctuations in catch were substantial. The proportion female:male was 1.77:1. Length-weight relations were: W = 0.00000791TL3.08 (W = weight, TL = total length) for females and W = 0.000175TL2.47 for males. There were an intense recruitment pulse in April and a minor one in September. Sizes of first sexual maturity were 180 mm TL for females and 170 mm TL for males. Parameters of the von Bertalanffy growth function were: LÂ¥ = 374 mm TL, kÂ =Â 1.27 year”“1 and t0 = 0.27 year for females; LÂ¥ = 313 mm TL, k = 1.78 year”“1 and t0 = ”“0.46 year for males. Available information suggests that catch of striped mojarra follows Lake Maracaibo natural periodic tidal-discharge rhythms. Evidence presented in this paper suggests that if either the tidal or the discharge patterns are changed, catches of strip mojarra may be affected. Striped mojarra make up an abundant fish resource that plays important ecological and fishery roles in Lake Maracaibo. Given the increasing fishery importance of striped mojarra, initiatives should be developed to protect its population in Lake Maracaibo.